Radio's second century : past, present, and future perspectives - Hendricks, John Allen (Rutgers University Press, 2020)
"As one of the first scholarly monographs to examine the status of broadcasting on its one hundredth anniversary, Radio's Second Century investigates both vanguard and perennial topics relevant to radio's past, present, and future. As the radio industry enters its second century of existence, it continues to be a dominant mass medium with almost total listenership saturation despite rapid technological advancements that provide alternatives for consumers. Lasting influences such as on-air personalities, audience behavior, fan relationships, and localism are analyzed as well as contemporary issues including social and digital media. Other essays examine the regulatory concerns that continue to exist for public radio, commercial radio, and community radio, and discuss the hindrances and challenges posed by government regulation with an emphasis on both American and international perspectives. Radio's impact on cultural hegemony through creative programming content in the areas of religion, ethnic inclusivity, and gender parity is also explored. Taken together, this volume compromises a meaningful insight into the broadcast industry's continuing power to inform and entertain listeners around the world via its oldest mass medium--radio"--